“Telling it in our own way”: Doing music-enhanced interviews with people displaced by violence in Colombia - Hazel Marsh; M. Teresa Amijos; Roger Few (New Area Studies)
In Colombia, five decades of violent conflict have displaced millions of people, many of whom now face severe risks from flooding, landslides and other environmental hazards in the places they have found to resettle. In our research, one of our main objectives was to better understand the experiences, vulnerabilities and survival strategies of conflict-displaced people living in hazard-prone locations in Soacha, an urban working-class district of Cundinamarca in the centre of Colombia, and in urban and peri-urban areas in or near Pereira and Manizales, both of which are cities in Colombia’s main coffee-growing region. We wanted to create spaces within which such people could tell their life stories with dignity and agency. For socially and politically marginalised people who have suffered enormous loss and trauma, and the disempowering effects of violence, conventional social science interviews may re-open wounds and cause extreme distress. Furthermore, interviewees may feel that there are ‘good’, ‘bad’ or otherwise ‘preferred’ answers to the questions they are asked. In our research, we instead invited participants to share a piece of music or a song they valued with us, via mp3 players, before opening a conversation about their life stories. In this way, we intended for participants to ‘territorialise’ the research encounter by creating comfortable spaces where their taste and habits were central (Dos Santos and Wagner, 2018), and where they exercised greater control and agency to decide the topics discussed (Levell, 2019). We wanted the songs people shared with us to act as their chosen entry points into their life stories. This article offers some reflections on how talking about music, a cultural form linked closely with emotions, memory and identity, can provide a resource for better understanding the lives and experiences of others.